Endoscopic Repair of the Distal Biceps Tendon - Steven Bokshan, M.D. (Arthroscopy Techniques)
Distal biceps ruptures are common orthopaedic injuries that may result in cosmetic deformity, loss of subjective flexion strength, and loss of objective supination strength if treated nonoperatively. To combat this, both single- and dual-incision techniques have been developed to repair the distal biceps. Although each of these procedures has unique complications, both procedures are at risk of posterior interosseous nerve palsies, with up to 21% of surgeons reporting nerve palsies. This article proposes an endoscopically assisted biceps tendon repair that uses minimal retraction of the muscles in the forearm, which may lower the risk of traction-related nerve palsy. In addition, direct visualization of the radial tuberosity with a small-joint arthroscope allows for ideal placement of suture anchors on the native footprints of the short head and long head insertions of the biceps tendon.